Processes governing nutrient dynamics in tropical urban-agriculture rivers, NE Thailand - Bridhikitti A. (2023)
Eutrophication induced water quality deterioration is typically found in urban–agricultural environments, especially in tropical cities. This study aims to understand processes governing nutrient dynamics in surface running waters at three cities in NE Thailand. Sampling was performed in both dry and wet seasons. The sampling sites exhibited different hydro-morphological characteristics. The results showed high NH3 concentration, exceeding the national standard, and high PO43−, classified as eutrophic water. The N:P ratio, however, was typically below the Redfield ratio for optimal algal growth. Stepwise linear regression models describe the processes governing loss and supply of TKN, NH3, NO3−, and PO43− in the urban river waters. The processes include upstream dilution, sorption/desorption, resuspension, urban wastewater discharge, and biological processes. The findings suggested that urban nutrient management should focus on minimizing NH3 and PO43−, preferably by proper wastewater and stormwater collection, upstream soil–water conservation, and river bed maintenance.